Research on the Model of Distance Education Resource Integration from the Perspective of Comparative Education - Zhao Dan (Journal of Mathematics)
In order to solve the problems of high data loss rate, long time-consuming resource integration, large amount of redundant data, and incomplete results of resource integration in traditional methods, a design method of distance education resource integration model from the perspective of comparative education is proposed. Association rules are used to mine resources and get effective resources in the context of comparative pedagogy, with the goal of increasing the impact of resource integration. Then, using a three-tier architecture, a remote education resource integration model is created, and the mining results are combined through the application layer, resource encryption layer, and multicast communication layer to achieve distance education resource integration. Simulation results show that the method of this article has low data loss rate, short resource integration time, less redundant data, and comprehensive integration results, which provides an effective technical support for the development of education.